Конструкторско-технологические варианты коммутационных плат с подложкой из кремния - Spirin, V. G. (PE "Politekhperiodika", Book and Journal Publishers, 2005)
The design and technological options of switching boards with a silicon substrate featuring two and three switching levels are considered, based on well-established industrial technologies. The use of these boards ensures the maximum possible packing density of microassemblies at a relatively low production cost.